Effects of hydrophobicity on splash erosion of model soil particles by a single water drop impact. Issue 11 (8th January 2013) - Ahn, Sujung; Doerr, Stefan H.; Douglas, Peter; Bryant, Robert; Hamlett, Christopher A.E.; McHale, Glen; Newton, Michael I.; Shirtcliffe, Neil J.
ABSTRACT: Raindrop impact can be a major contributor to particle mobilization for soils and other granular materials. In previous work, water repellent soils, comprised of hydrophobic particles, have been shown to exhibit greater splash erosion losses under multiple drop impact. However, the underlying principle differences in splash behavior between hydrophobic and hydrophilic granular surfaces have not been studied to date. In this study the effects of particle hydrophobicity on splash behaviour by a single water drop impact were examined using high‐speed videography. Water drops (4 mm in diameter) were dropped on beds of hydrophilic and hydrophobic glass beads (sieved range: 350–400 µm), serving as model soil particles. The drop velocity on impact was 2.67 m s ‐1, which corresponds to ~30% of the terminal velocity of a raindrop of similar size. The resulting impact behaviour was measured in terms of the trajectories of particles ejected from the beds and their final resting positions. The response to the impacting water drop was significantly different between hydrophilic and hydrophobic particles in terms of the distance distribution, the median distance travelled by the particles and number of ejected particles. The greater ejection distances of hydrophobic particles were mainly the result of the higher initial velocities rather than differences in ejecting angles. The higher and longer ejection trajectories for hydrophobic particles, compared with hydrophilic particles, indicate that particle hydrophobicity affects splash erosion from the initial stage of rainfall erosion before a water layer may be formed by accumulating drops. The ~10% increase in average splash distance for hydrophobic particles compared with hydrophilic particles suggests that particle hydrophobicity can result in greater net erosion rate, which would be amplified on sloping surfaces, for example, by ridges in ploughed agricultural soils or hillslopes following vegetation loss by clearing or wildfire. Copyright © 2012 John Wiley & Sons, Ltd.